Automated Image Analysis of Live/Dead Staining of the Fungus Aureobasidium pullulans on Microscope Slides and Leaf Surfaces. (October 2000) - Nelson, Christopher D.; Spear, Russell N.; Andrews, John H.
An image analysis program and protocol for the identification and enumeration of live versus dead cells of the yeast-like fungus Aureobasidium pullulans was developed for both populations on microscope slides and leaf surfaces. Live cells took up CellTracker Blue™, while nonviable cells stained with DEAD Red™. Image analysis macro programs running under Optimas™ software were used to acquire images and to differentiate and enumerate viable from nonviable cells. The software was capable of discriminating green as a third parameter for identification and quantification of green fluorescent protein-expressing cells in a wild-type population.